Desenvolvimento de um dispositivo IOT lúdico para monitoramento de variáveis ambientais - Brezolin, Fábio Lopes (2018)
This dissertation presents the developing an IoT device for educational purposes, including the evaluationm of its potentiality, by users without technical knowledge about the operation of this technology. A prototype was developed and equipped with sensors that capture data from environmental variables and display information locally and also in a web interface. The project integrates three main aspects: technology, people and resource management through IoT. IoT resource management was realized through agile access and designed with a simplified authentication methodology to access the features of the developed device. To evaluate this prototype, tests were conducted with groups of students that interacted with theIoT device and with a web interface linked to it, registering their impressions about the functioning of the device ecosystem. The objective of the evaluations with the users was to verify the feasibility of incorporating an IoT device in the classroom, more specifically for elementary students, in an intuitive way and aiming to stimulate a fast acceptance of this technology on their daily life. The validation of the authentication process made it possible to deepen the study and analysis of the interaction between people and IoT devices, considering aspects such as the visual appearance of the device, personalization and integration of other technologies, such as touchscreen. It was also verified that the simplified authentication model is suitable for use in small environments, such as the classroom, exemplifying an authentication model that is fast and suitable for the mobility of IoT devices, as an alternative to conventional solutions.